Adherence to the EAT-lancet dietary pattern among older adults in Rwanda and its association with micronutrient intake - Habumugisha, Theogene; Stubbendorff, Anna ; 0000-0001-9851-6213; Tembo, Penias; Matsiko, Eric; Måren, Inger Elisabeth; Kaiser, Matthias; Borgonjen-van den Berg, Karin; Melse-Boonstra, Alida; Engebretsen, Ingunn M S; Dierkes, Jutta (Food & Nutrition Research, 2025)
BACKGROUND: Sub-Saharan Africa is facing a dietary transition with both undernutrition and rising rates of non-communicable diseases. Adopting the reference diet proposed by the EAT-Lancet Commission can reduce both the environmental burden and improve health outcomes. However, whether this diet provides micronutrient adequacy in older adults in low-income settings has not been investigated. This study examines adherence to the EAT-Lancet diet and its association with micronutrient intake among older adults in the Gasabo district, Kigali, Rwanda. METHODS: This cross-sectional study involved 334 older adults aged 55-93 years from Kigali, Rwanda. Dietary intake was assessed using two non-consecutive 24-h recalls, and socio-demographic data were collected through interviews. Adherence to the EAT-Lancet diet was evaluated using a 42-point index based on food group consumption and micronutrient intake was analyzed in relation to adherence tertiles. Multivariable regression models, adjusted for age, sex, and energy intake, were used to assess associations between diet adherence and micronutrient intake. RESULTS: The EAT-Lancet adherence score ranged from 13 to 36, with a mean of 24. Higher adherence was associated with increased consumption of whole grains, vegetables, fish, and nuts, while red meat, dairy, and poultry intake declined. Adherence was positively associated with energy intake and intake of retinol-equivalents, thiamine, niacin, folate, vitamins B12 and D, calcium, phosphorus, magnesium, iron, and zinc. When adjusting for energy intake, the association with zinc and potassium became non-significant and the association with riboflavin became negative. CONCLUSION: Higher adherence to the EAT-Lancet diet was associated with higher intake of energy and several micronutrients important for healthy aging in this population of predominantly older, poor adults in Kigali. However, the potential for nutrient gaps, particularly in riboflavin, highlights the need for context-specific dietary adaptations to ensure nutritional adequacy in older populations in Rwanda.
© 2025 Theogene Habumugisha et al.